Mixed blessings: laws, religions and women's rights in the Asia-Pacific region - Whiting, Amanda; Evans, Carolyn (Studies in religion, secular beliefs and human rights, 2006)
Ch. 1.Situating the issues, framing the analysis /Carolyn Evans and Amanda Whiting --Ch. 2.Sex or Sangha? : non-normative gender roles for women in Thai law and religion /Lucinda Peach --Ch. 3.Women and witchcraft : positivist, prelapsarian, and post-modern judicial interpretations in PNG /Jean G. Zorn --Ch. 4.Between a rock and a hard place : women, religion, and law in Solomon islands /Jennifer Corrin Care --Ch. 5.Women, religion, and the law in Aotearoa/New Zealand : the complexity of accommodating different value systems in law /Margaret Bedggood and Leah Whiu --Ch. 6.The Roman Catholic Church and the rights of East Timorese women /Susan Harris Rimmer.